Estudo da resposta pulpar após o uso de diferentes materiais capeadores em pulpotomias - Junqueira, Marina Azevedo (2015)
The purpose of the present study was to evaluate histologically the inflammatory reaction of rat molar pulp tissue after pulpotomy performed with white MTA and 15.5% Ferric Sulfate, at 24, 48 and 72 hours, as well as the clinic, radiographic and histological response of the dentin-pulp complex of human primary molars until 18 months after pulpotomy with the same capping agents. Twenty six Wistar rats were used, randomly distributed into 2 groups (MTA and Ferric Sulfate) and divided into 3 subgroups, according to the experimental period (24, 48 and 72 hours). The teeth were prepared and subsequently stained with hematoxylin and eosin (HE) to perform histological analysis. All the teeth evaluated preserved the vitality of the remaining radicular pulp. Hyperemic blood vessels and variable concentrations of neutrophils were observed in both groups, which characterized different levels of inflammation in the cervical third of the radicular pulp. Larger inflammatory infiltrate was detected at 24 hours, which decreased after 48 and 72 hours. For the human study, 31 lower or upper primary molars from 19 children aging between 6 and 9 years old were selected, randomly distributed into two groups (MTA and Ferric Sulfate) and clinically and radiographically evaluated at 3, 6, 12 and 18 months. The teeth at the exfoliation period underwent surgical removal and were prepared and stained for histology. All of the teeth treated with MTA presented clinical and radiographic success over the experimental period. One tooth treated with Ferric Sulfate presented interradicular lesion at 18 months. None of the teeth had mobility, fistula, inflammation or swelling in the gingival tissue. Histologically, the teeth treated with MTA presented dentin barrier formation and subjacent connective tissue with normal features. Some teeth treated with Ferric Sulfate had tissue necrosis, chronic inflammation and radicular stenosis; other teeth presented normal connective tissue and radicular stenosis. Taken together, our results allow us to conclude that both materials were effective for pulpotomy of primary teeth and caused similar inflammatory reaction, decreasing over time in rat molars.